What happens to the physical and psychosocial work environment when activity-based offices are introduced into academia?. Issue 4 (8th November 2018) - Berthelsen, Hanne; Muhonen, Tuija; Toivanen, Susanna
Abstract : Purpose: There is an increased interest for introducing activity-based offices at universities. The purpose of this study is to contribute to the knowledge about the importance of the built environment for the psychosocial work environment within academia by analyzing how staff at a large Swedish university experienced the physical and psychosocial work environment before and after moving to activity-based offices. Design/methodology/approach: A Web-based survey was distributed to all employees at two faculties at a university three months before (2015, n = 217, response rate 51 per cent) and nine months after (2016, n = 200, response rate 47 per cent) relocation to a new activity-based university building. Findings: In the new premises, a vast majority (86 per cent) always occupied the same place when possible, and worked also more often from home. The social community at work had declined and social support from colleagues and supervisors was perceived to have decreased. The participants reported a lower job satisfaction after the relocation and were more likely to seek new jobs. No aspects in the physical or psychosocial work environment were found to have improved after the relocation. Research/limitations implications: The study had a two-wave cross-sectional design, which does not allow establishing causal relations. Practical implications: There is reason to be cautious about relocation to activity-based offices at universities. The potential savings in costs for premises may lead to may be followed by an increase in other costs. The risk that staff cannot concentrate on their work in activity-based university workplaces and lose their sense of community with colleagues are factors, which in the long run may lead to decreased efficiency, more conflicts and poorer well-being. Originality/value: This paper contributes with new knowledge concerning changes in the physical and psychosocial work environment when relocating from cell offices to activity-based offices in a university setting.